Analisis Kemampuan Pemecahan Masalah Mahasiswa Fisika Semester Menengah dalam Mata Kuliah Fisika Inti - Fadhila, Fadhila; Yunus, Ayyub; Saz, Jushadi Arman (Journal of Health, Education, Economics, Science, and Technology, 2025)
Problem-solving ability is a key competence in physics education; however, many physics education students still struggle to apply scientific thinking processes systematically, particularly in the Nuclear Physics course. This study aims to analyze the problem-solving abilities of mid-level physics education students based on the stages of Polya's model. A descriptive quantitative approach was employed, involving two classes of fifth-semester students at the University of West Sulawesi. Data were collected through validated open-ended problem-solving tests and analyzed using descriptive techniques. The results show that 67% of students encountered difficulties in understanding the problem, 83% struggled with planning and executing solutions, and all students (100%) faced obstacles in reviewing their solutions. These findings indicate weak reflective and strategic thinking skills among students and highlight the need for the explicit integration of problem-solving models in instruction. The implications emphasize the importance of designing learning experiences that focus not only on final outcomes but also on fostering scientific thinking processes to prepare students as competent future physics educators..